Longevity, Retirement and Intra-Generational Equity - Svend E. Hougaard Jensen; Thorsteinn Sigurdur Sveinsson; Gylfi Zoega (Center for Economic Studies and ifo Institute (CESifo), 2019)
We find that segments of society who have shorter life expectancy can expect a lower retirement income and lifetime utility due to the longevity of other groups participating in the same pension scheme. Linking retirement age to average life expectancy magnifies the negative effect on the lifetime utility of those who suffer low longevity. Furthermore, when the income of those with greater longevity increases, those with shorter life expectancy become even worse off. Conversely, when the income of those with shorter life expectancy increases, they end up paying more into the pension scheme, which benefits those who live longer. The relative sizes of the low and high longevity groups in the population determine the magnitude of these effects. We calibrate the model based on data on differences in life expectancy of men and women and find that males suffer from a 10 percent drop in the amount of pension benefits from being forced to pay into the same scheme as females.
Keywords: E21; E24; 330; longevity; pension age; retirement; inequality